Republic of Armenia : Third Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Alternate Executive Director and Advisor for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2010)
Armenia's third review under the Stand-By Arrangement and its request for Waiver of Nonobservance of Performance Criterion are discussed. The uptick in inflation was largely driven by exogenous factors, but it is important that these do not feed into further inflationary expectations. The financial sector has been resilient to the crisis and almost all banks are well capitalized. The fiscal stimulus has appropriately supported the economy during the crisis and maintaining priority public spending has been critical for mitigating the impact of the crisis on the poor.